2017
DOI: 10.1002/ijch.201700066
|View full text |Cite
|
Sign up to set email alerts
|

A DFT Survey of the Effects of d‐Electron Count and Metal Identity on the Activation and Functionalization of C−H Bonds for Mid to Late Transition Metals

Abstract: The contribution of metal identity to the activation and functionalization of methane by a series of three‐coordinate imide complexes is evaluated in silico for a 3‐by‐3 block of metals from Fe to Pt. Three mechanisms were studied: oxidative addition (OA) to the metal; hydrogen atom abstraction (HAA) by the imide nitrogen; and, [2+2] addition across the metal‐imide bond. In no studied case, was a [2+2] mechanism preferred, perhaps suggesting this mechanism is largely (entirely?) the domain of d0 imides. There … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Thermodynamic stability or the lack thereof of a metal–ligand bond, or the σ- and π-components of a multiple-bond, is key to many practical applications in inorganic and organometallic chemistry, especially in the area of transition metal catalysis. To wit, Simões and Beauchamp, in their classic review, refer to metal–carbon and metal–hydrogen bond energies as “the keys to catalysis.” It is well-known that steric and electronic effects of supporting ligands can impact the stability and the reactivity of known organometallic catalysts and even to predict the hypothetical synthesis of new complexes. , For example, in a previous study of methane activation by nine metal–imide (L n MNR) complexes incorporating metals from Groups 8–10, it was deduced that the strength of a metal–imide π-bond was a key property in determining the preferred activation mechanism …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thermodynamic stability or the lack thereof of a metal–ligand bond, or the σ- and π-components of a multiple-bond, is key to many practical applications in inorganic and organometallic chemistry, especially in the area of transition metal catalysis. To wit, Simões and Beauchamp, in their classic review, refer to metal–carbon and metal–hydrogen bond energies as “the keys to catalysis.” It is well-known that steric and electronic effects of supporting ligands can impact the stability and the reactivity of known organometallic catalysts and even to predict the hypothetical synthesis of new complexes. , For example, in a previous study of methane activation by nine metal–imide (L n MNR) complexes incorporating metals from Groups 8–10, it was deduced that the strength of a metal–imide π-bond was a key property in determining the preferred activation mechanism …”
Section: Introductionmentioning
confidence: 99%
“…2,3 For example, in a previous study of methane activation by nine metal−imide (L n MNR) complexes incorporating metals from Groups 8− 10, it was deduced that the strength of a metal−imide π-bond was a key property in determining the preferred activation mechanism. 4 Unfortunately, experimental thermodynamic data for metal− ligand bonds are often very sparse, and essentially nonexistent for bond energy components like σand π-bond strengths, especially for large, catalytically relevant transition metal complexes. 5 This gap in the literature exists because accurate experimental measurements are generally difficult to obtain for the thermochemistry of metal-containing complexes.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Previous studies have revealed that C–H bond activation is the rate-determining step of the catalytic methane oxidation. 6 11 Therefore most of the research reported so far aimed at revealing the factors that facilitate this reaction step, and attempted to establish structure–activity relationships that would guide the development and optimization of the promising catalytic systems. 12 16 Such factors as the radical character of the oxygen centre 17 , 18 in the reactive metal-oxo active site or its hydrogen affinity 12 were proposed as the suitable activity descriptors for the successful C–H activation catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 For example, Moulder and Cundari observed in a methane C−H activation study by imide complexes (L n MNR, M = group 8−10 metals) that the strength of the metal−imide π-bond and how this thermodynamic quantity was modulated as a function of metal identitywas a critical factor in determining the preferred activation mechanism: [2 + 2] versus oxidative addition versus hydrogen atom abstraction. 4 The early 4d and 5d transition metals are "green" in both economic and ecological senses, Figure 1, and are widely used in industrial catalysis. 5 Many olefin metathesis catalysts have heavy, early transition metal centers such as molybdenum and tungsten, Schrock's catalysts being a notable example.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The criticality of metal–carbon and metal–hydrogen bond energies is reflected in their reference as “the keys to catalysis” by Simões and Beauchamp in a classic review on transition metal thermochemistry . Stability, and thereby reactivity, can thus be altered through covalent, electrostatic, steric, and so forth effects imparted by the supporting ligands upon the metal and substituents on the actor ligand for organometallic catalysts in predictable, albeit typically not quantifiable, ways. , For example, Moulder and Cundari observed in a methane C–H activation study by imide complexes (L n MNR, M = group 8–10 metals) that the strength of the metal–imide π-bondand how this thermodynamic quantity was modulated as a function of metal identitywas a critical factor in determining the preferred activation mechanism: [2 + 2] versus oxidative addition versus hydrogen atom abstraction …”
Section: Introductionmentioning
confidence: 99%